2021
DOI: 10.1182/blood-2021-148492
|View full text |Cite
|
Sign up to set email alerts
|

Genomic Analysis Focusing on RUNX1-RUNX1T1 in Japanese Patients with AML: HM-Screen-Japan 01

Abstract: Background and Methods: Acute myeloid leukemia (AML) bearing the RUNX1-RUNX1T1 fusion gene is known to be one of the core-binding factor AML (CBF-AML) which exerts relatively good prognosis. The RUNX1-RUNX1T1 fusion gene are present in approximately 3.5% of patients with AML (data from cBioPortal). However, the real-world epidemiology of this mutation and co-existing gene alterations have not been fully investigated in Japan. We launched an actionable mutation profiling multicenter study named H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 0 publications
1
2
0
Order By: Relevance
“…These data suggested that KIT mutations, especially those in exon 17, are related to a poor prognosis in AML with RUNX1-RUNX1T1, consistent with previous reports on the genetic profiling of R/R AML in patients with de novo AML [7,11,48,49,52]. Based on our analysis of all cases in HM-SCREEN-Japan-01, KIT mutations represented the predictor with the worst outcomes of all assessed gene mutations [53,55]. Most of the surviving patients had received allo-HSCT, regardless of whether they had been diagnosed with CBF or non-CBF leukemia in R/R cases (Supplementary Materials).…”
Section: Clinical Impact Of Kit Mutation In Unfit and R/r Amlsupporting
confidence: 90%
See 2 more Smart Citations
“…These data suggested that KIT mutations, especially those in exon 17, are related to a poor prognosis in AML with RUNX1-RUNX1T1, consistent with previous reports on the genetic profiling of R/R AML in patients with de novo AML [7,11,48,49,52]. Based on our analysis of all cases in HM-SCREEN-Japan-01, KIT mutations represented the predictor with the worst outcomes of all assessed gene mutations [53,55]. Most of the surviving patients had received allo-HSCT, regardless of whether they had been diagnosed with CBF or non-CBF leukemia in R/R cases (Supplementary Materials).…”
Section: Clinical Impact Of Kit Mutation In Unfit and R/r Amlsupporting
confidence: 90%
“…Hematologic Malignancy (HM)-SCREEN-Japan-01 (UMIN000035233) is a genome profiling study of patients newly diagnosed with adult AML who are unsuitable for the standard first-line treatment (unfit) or have relapsed/refractory (R/R) AML [53][54][55] (methods are described in Supplementary Materials). The objective of the present study was to evaluate the frequency and characteristics of cancer-related genomic alterations in patients with AML using a comprehensive genome profiling assay (FoundationOne ® Heme (F1H)) and to determine the quality of specimens used in gene analysis.…”
Section: Kit Mutation In Unfit and Relapsed/refractory Aml: Results F...mentioning
confidence: 99%
See 1 more Smart Citation